2007
DOI: 10.1590/s0100-41582007000100011
|View full text |Cite
|
Sign up to set email alerts
|

Controle biológico de Monosporascus cannonballus com Chaetomium

Abstract: O colapso do meloeiro (Cucumis melo), causado por Monosporascus cannonballus, é uma das principais enfermidades que acometem esta olerícola. O presente trabalho objetivou estudar o potencial do controle biológico de M. cannonballus com Chaetomium. Substrato infestado com 0,5; 1; 2; 4 e 8 x 10(5) UFC g-1 de Chaetomium foi colocado em bandejas, nas quais sementes de meloeiro do tipo Pele de Sapo cv. PS 1430 foram semeadas após duas semanas de incubação. As mudas obtidas foram transplantadas para vasos com substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…(3,2 x 10 5 ufc/mL), Pseudomonas spp. (1,5 x 10 4 ufc/mL) e, em menor escala, actinobactérias (1,1 x 10 2 ufc/mL), que são organismos estudados para o controle biológico de diversas doenças de plantas (Janisiewicz & Jeffers, 1997;Sales Júnior et al, 2007). Os dados populacionais encontrados no biofertilizante diferem dos encontrados por Kupper et al (2006) FIGURA 1 -Efeito do leite, Bacillus subtilis (Bs7 = 10 7 ufc/mL; Bs8 = 10 8 ufc/mL), meio de cultura para fermentação de Bacillus (0,5% de melaço + 0,5% de milhocina e 0,3% de fosfato monobásico), Trichoderma harzianum (Th = 10 6 conídios/mL) e biofertilizante como testemunha (Biof.)…”
Section: Resultsunclassified
“…(3,2 x 10 5 ufc/mL), Pseudomonas spp. (1,5 x 10 4 ufc/mL) e, em menor escala, actinobactérias (1,1 x 10 2 ufc/mL), que são organismos estudados para o controle biológico de diversas doenças de plantas (Janisiewicz & Jeffers, 1997;Sales Júnior et al, 2007). Os dados populacionais encontrados no biofertilizante diferem dos encontrados por Kupper et al (2006) FIGURA 1 -Efeito do leite, Bacillus subtilis (Bs7 = 10 7 ufc/mL; Bs8 = 10 8 ufc/mL), meio de cultura para fermentação de Bacillus (0,5% de melaço + 0,5% de milhocina e 0,3% de fosfato monobásico), Trichoderma harzianum (Th = 10 6 conídios/mL) e biofertilizante como testemunha (Biof.)…”
Section: Resultsunclassified
“…Several studies have reported different management strategies to control MRRVD, such as the use of green fertilization (Sales Júnior, Senhor, Michereff, & Medeiros, ), application of fumigants (Stanghellini et al., ), destruction of postharvest plant residues (Radewald, Ferrin, & Stanghellini, ), chemical control (Pivonia, Gerstl, Maduel, Levita, & Cohen, ), application of essential oils (Awad, ; Fernandes et al., ), the use of plant growth‐promoting bacteria (Antonelli, Reda, Aleandri, Varvaro, & Chilosi, ) and antagonistic biocontrol agents (Aleandri, Martignoni, Reda, & Chilosi, ; Sales Júnior et al., ; Zhang, Bruton, Howell, & Miller, ), and grafting on Cucurbita hybrid rootstocks (Al‐Mawaali, Al‐Sadi, Al‐Said, & Deadman, ; Beltrán, Vicent, García‐Jiménez, & Armengol, ; Edelstein et al., ). However, some of these techniques are not sufficient if applied alone but can be effective when sustainable measures are integrated (Medeiros et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The expansion of these cucurbits, associated with intensive and continuous cultivation, without crop rotation, has increased the incidence and severity of root diseases, which are responsible for the higher losses of productivity and quality of commercialized fruits (Sales Júnior et al, 2007;Senhor et al, 2009). Among the diseases, Monosporascus root rot and vine decline (MRRVD), caused by the fungus Monosporascus cannonballus Pollack & Uecker, is widely disseminated in the main producing areas…”
Section: Introductionmentioning
confidence: 99%